Civics education in the United States - Seavy, Andrew (Kansas State University, 2022)
High quality civics education is a vital, yet often overlooked, feature of a healthy democratic society. Due to decades of neglect at the hands of an indifferent public and government, civics education in the United States is significantly behind other topics (such as Science, Technology, Engineering, and Mathematics, commonly referred to as STEM), and as such, civic knowledge in the United States is low. In this report, several articles regarding the state of civics education in the US are reviewed, and then three programs to improve civics education are explored. Articles reviewed include one “report card” on various civics education programs and statistical evidence to support the assertions of low civic knowledge and low spending on civics education. Programs explored include the James Madison Memorial Fellowship, We the People, and Educating for American Democracy.
Keywords: Civics education; We the People; Educating for American Democracy